Probióticos en pollos parrilleros: Una estrategia para los modelos productivos intensivos - Blajman, Jesica (2015)
The broiler industry has become an important economic activity in Argentina. Glo-bal production of broiler meat has been growing in Argentina faster than for any other meats,possibly due to declining poultry prices and increasing incomes. Modern rearing systems canproduce broilers ready to slaughter in 50 days, with the required 2.7 kg of weight and a feedconversion of about 1.6 kg feed/kg of meat. Nevertheless, broilers raised under these intensiveconditions are exposed to various stressors every day. For many years, feed supplementationwith antibiotics was widely used to stabilize the gut flora, improve general parameters andprevent avian diseases. However, the utility of antibiotics has been questioned because of theemergence and spread of antibiotic-resistant bacteria in meat. Therefore, there is a renewedinterest in finding viable alternatives to antibiotics. One potential method is the supplemen-tation of broiler diets with probiotics. This review provides an updated summary of the use ofprobiotics to improve sanitary conditions and enhance performance in broilers, demonstratingthe role of probiotics as a reliable option to replace antimicrobial growth promoters.